PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN PENGALAMAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA THE BALCONE SUITES & RESORT - Sri Kemala; Fira Olivia Krisanti; Diah Permata; Almasdi Almasdi (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This research aims to see the influence of service quality on customer loyalty and the customer experience as an intervening variable at The Balcone Suites & Resort. This research uses quantitative methods, and then the data is processed and analysed using the Structural Equation Modelling—Partial Least Squares (SEM-PLS) method. The number of research respondents was 110. The results of this research show that (1) there is a positive and significant influence between Tangible and customer loyalty at The Balcone Suites & Resort. (2) There is a negative and insignificant influence between reliability and empathy on customer loyalty at The Balcone Suites & Resort. (3) There is a positive but not significant influence between responsiveness, assurance, and customer loyalty at The Balcone Suites & Resort. (4) There is a positive but not significant influence between tangibility, reliability, responsiveness, assurance, and empathy on the customer experience at The Balcone Suites & Resort. (5) There is a positive and significant influence between customer experience and customer loyalty at The Balcone Suites & Resort. (6) There is a positive and significant influence between Tangible on Customer Loyalty and Customer Experience as an Intervening Variable at The Balcone Suites & Resort. (7) There is a positive but not significant influence between reliability, responsiveness, assurance, and empathy on customer loyalty, with customer experience as an intervening variable at The Balcone Suites & Resort. Penelitian ini bertujuan untuk melihat pengaruh Kualitas Pelayanan terhadap Loyalitas Pelanggan dengan Pengalaman Pelanggan sebagai Variabel Intervening pada The Balcone Suites & Resort. Penelitian ini menggunakan metode kuantitatif, kemudian data diolah dan dianalisis menggunakan metode Structural Equation Modelling – Partial Least Square (SEM-PLS). Responden penelitian berjumlah 110 orang. Hasil penelitian ini menunjukkan bahwa: (1) Terdapat Pengaruh positif dan signifikan antara Tangible terhadap Loyalitas Pelanggan di The Balcone Suites & Resort. (2) Terdapat Pengaruh negatif dan tidak signifikan antara Reliability dan Empathy terhadap Loyalitas Pelanggan di The Balcone Suites & Resort. (3) Terdapat Pengaruh positif tetapi tidak signifikan antara Responsivenes, Assurance, terhadap Loyalitas Pelanggan di The Balcone Suites & Resort. (4) Terdapat Pengaruh positif tetapi tidak signifikan antara Tangible, Reliability, Responsiveness, Assurance, dan Empathy terhadap Pengalaman Pelanggan di The Balcone Suites & Resort. (5) Terdapat Pengaruh positif dan signifikan antara Pengalaman Pelanggan terhadap Loyalitas Pelanggan di The Balcone Suites & Resort. (6) Terdapat Pengaruh positif dan signifikan antara Tangible terhadap Loyalitas Pelanggan dengan Pengalaman Pelanggan sebagai Variabel Intervening di The Balcone Suites & Resort. (7) Terdapat Pengaruh positif tetapi tidak signifikan antara Reliability, Responsiveness, Assurance, dan Empathy terhadap Loyalitas Pelanggan dengan Pengalaman Pelanggan sebagai Variabel Intervening di The Balcone Suites & Resort.